Identification of Active Compounds and Antidiabetic Activity of Red Shoot (Syzygium myrtifolium) Leaves Extract With In Vitro and In Silico Methods - Prakoso, Muhamad Iqbal; Warnasih, Siti (Pharmaceutical Sciences and Research, 2026)
Diabetes mellitus (DM) is a chronic metabolic disease that affects approximately 537 million people worldwide (1 in 10 individuals), and its prevalence is projected to reach 783 million by 2045. One of the plants that has the potential to be an antidiabetic is red shoots (Syzygium myrtifolium) since it contains various secondary metabolite compounds such as flavonoids, triterpenoids, steroids, saponins, phenolics, and anthocyanins. This study aimed to evaluate the antidiabetic properties of red shoot leaves extract and to identify and predict interactions between its active compounds and the α-glucosidase receptor. Ethanol, ethyl acetate, and n-hexane extracts of red shoot leaves were tested in vitro method for α-glucosidase inhibitory activity. The most active extract was analyzed using gas chromatography–mass spectrometry (GC–MS) to identify its chemical constituents. The identified compounds were then tested in silico using the molecular docking method to simulate interactions with the α-glucosidase receptor. The ethanol extract showed the strongest α-glucosidase inhibitory activity (IC₅₀ = 83.69 ppm), as compared to the ethyl acetate and n-hexane extracts. GC–MS analysis identified 5 secondary metabolites, predominantly terpenoids. Molecular docking revealed that three compounds includes α-Gurgujene, farnesyl acetate and Neophytadiene exhibited strong binding affinities (ΔG), hydrogen bonds and nteractions with the same amino acid residues as the standard control acarbose, indicating potential α-glucosidase inhibitory activity. These findings suggest that red shoot leaves extract, particularly its ethanol extract, contains bioactive compounds with promising potential as natural antidiabetic agents, warranting further pharmacological and clinical investigation.